TI_GERICHTE 16.2022.50 vom 3. August 2023 , Proprietà per piani: nomina dell'amministratore - reclamo divenuto privo di oggetto - TI Tribunale d'appello (2023)
Proprietà per piani: nomina dell'amministratore - reclamo divenuto privo di oggetto